Crisis in the Philippines the Marcos era and beyond - Bresnan, John 1927-2006 (Princeton University Press, 1986)
The book provides an overview of the history of the Philippines from the period of Spanish colonial domination to the present and analyzes the twenty-year Marcos record and the causes of the downfall of the Marcos regime. The essays will greatly aid the general reader in understanding the Philippine-American relationship. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press.